Pengaruh Model RADEC (Read, Answer, Discuss, Explain, Create) dan Motivasi Belajar Terhadap Keterampilan Menulis Teks Eksposisi Siswa - As-syfa Rumaisya Fadil; Syahrul Ramadhan (Ranah: Jurnal Kajian Bahasa, 2023)
Research into the impact of the RADEC model on expository text writing proficiency is crucial as it presents a comprehensive methodology linked to various steps, from reading to creating content. This study is expected to provide an understanding of the extent to which the RADEC model can be an answer to address writing proficiency issues. The objectives of this research are (1) to understand the effect of RADEC model and conventional model on exposition text writing proficiency; (2) to understand the effect of RADEC learning model on exposition text writing proficiency of students with high learning drive; (3) to understand the effect of RADEC model on writing proficiency of students with low drive; and (4) to understand the relationship between RADEC model and learning drive in influencing exposition text writing proficiency. This research applied experimental technique with quantitative methodology and the type was quasi experiment, and used 2x2 factorial design. The sample was taken by purposive sampling technique and obtained Class X E6 and X E5 as samples in this study. The results of hypothetical investigation and research show some significant results. First, there is an effect of proficiency in writing exposition texts for students taught using the RADEC model and proficiency in writing exposition texts for students taught using the conventional model.  Secondly, there is an effect of proficiency in writing exposition text for high learning motivation students taught using RADEC model and proficiency in writing exposition text for high learning motivation students taught using conventional model. Third, there is an effect of proficiency in writing exposition text for low learning motivation students taught with RADEC model and proficiency in writing exposition text for low learning motivation students taught with conventional model. Fourth, there is no interaction between RADEC learning model and learning motivation on the exposition text writing proficiency of Adabiah Padang high school grade X students because the FAB/Fcount is 1.81. Ftable at the significance level (α = 0.05) with dk for numerator = 1 (dbAB) and dk for denominator = 36 (n-ab) is 4.15. AbstrakPenelitian dampak model RADEC pada kemahiran menulis teks eksposisi krusial karena menyajikan metodologi komprehensif yang terkait dengan berbagai langkah, mulai dari membaca hingga membuat konten. Penelitian ini diharapkan dapat memberikan pemahaman tentang sejauh mana model RADEC dapat menjadi jawaban untuk mengatasi masalah kemahiran menulis. Tujuan dari riset ini, yaitu (1) memahami pengaruh model RADEC dan model konvensional terhadap kemahiran menulis teks eksposisi; (2) memahami pengaruh model pembelajaran RADEC terhadap kemahiran menulis teks eksposisi murid yang berdorongan belajar tinggi; (3) memahami pengaruh model RADEC terhadap kemahiran menulis murid yang penguasaan dorongan rendah; dan (4) memahami hubungan model RADEC dengan dorongan belajar dalam memengaruhi kemahiran menulis teks eksposisi. Penelitian ini menerapkan teknik eksperimen dengan metodologi kuantitatif dan jenisnya adalah eksperimen semu (quasi experiment), serta menggunakan desain factorial 2x2. Sampel diambil dengan metode purposive sampling dan mendapatkan Kelas X E6 dan X E5 sebagai sampel. Hasil penyelidikan hipotesis dan penelitian menunjukkan beberapa hasil yang signifikan. Pertama, terdapat pengaruh kemahiran menulis teks eksposisi siswa yang diajar menggunakan model RADEC dan kemahiran menulis teks eksposisi yang diajar dengan menggunakan model konvensional.  Kedua, terdapat pengaruh kemahiran menulis teks eksposisi untuk siswa berdorongan belajar tinggi yang diajarkan dengan menggunakan model RADEC dan kemahiran menulis teks eksposisi untuk siswa yang berdorongan belajar tinggi yang diajarkan dengan menggunakan model konvensional. Ketiga, terdapat pengaruh kemahiran menulis teks eksposisi untuk siswa berdorongan belajar rendah yang diajarkan dengan model RADEC dan kemahiran menulis teks eksposisi untuk siswa berdorongan belajar rendah yang diajarkan dengan model konvensional. Keempat, tidak terjadi interaksi antara model pembelajaran RADEC dengan dorongan belajar terhadap kemahiran menulis teks eksposisi siswa kelas X SMA Adabiah Padang karena diperoleh FAB/ Fhitung sebesar 1,81. Ftabel pada taraf signifikansi (α = 0,05) dengan dk untuk pembilang = 1 (dbAB) dan dk untuk penyebut = 36 (n-ab) adalah 4,15.